Implementation of Information Technology in Improving Effectiveness, Efficiency, and Productivity at PT. BPR BKK Muntilan (Perseroda): Penerapan Teknologi Informasi dalam Peningkatan Efektivitas, Efisiensi dan Produktivitas pada PT. BPR BKK Muntilan (Perseroda) - Tri Novianto; Arman Arman (Room of Civil Society Development, 2026)
The rapid development of information technology has encouraged banking institutions, including rural banks, to improve service quality, operational efficiency, and digital service capacity. This study aims to analyze the implementation of information technology at PT. BPR BKK Muntilan (Perseroda) and its contribution to operational effectiveness, work process efficiency, and digital service productivity. This research used a descriptive qualitative approach with a single case study design. Data were collected through observation, semi-structured interviews with six informants consisting of an operational director, an IT manager, two branch managers, and two operational staff, as well as documentation of internal transaction reports and IT-related documents. The findings show that the implementation of IBSBranchless Online supports faster transaction processing, easier customer data retrieval, more structured reporting, and reduced recording errors. The use of information technology also contributed to efficiency, as indicated by reduced data search time, paper usage, administrative costs, and transaction recording errors. Digital service productivity increased, as reflected in the rise of digital transactions from 45,179 records in 2022 to 134,068 records in 2025, with a peak of 145,771 records in 2024. However, the implementation still faces challenges, including limited IT infrastructure, insufficient employee training, and suboptimal system integration. This study recommends gradual infrastructure upgrades, continuous IT training, and API- or middleware-based system integration.